2021
DOI: 10.1093/rheumatology/keab695
|View full text |Cite
|
Sign up to set email alerts
|

Utility of interval kidney biopsy in ANCA-associated vasculitis

Abstract: Objectives Anti-neutrophil cytoplasm antibody (ANCA)-associated vasculitis (AAV) is a rare autoimmune disorder that commonly involves the kidney. Early identification of kidney involvement, assessing treatment-response and predicting outcome are important clinical challenges. Here, we assessed the potential utility of interval kidney biopsy in AAV. Methods In a tertiary referral centre with a dedicated vasculitis service, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
2
12
1
Order By: Relevance
“…Studies using repeated kidney biopsies in the case of persistent or worsening hematuria are essential to answer these questions. A small study with interval biopsies after a median time of 130 days indicated low agreement with clinically suspected active disease, which was found in only 41% of patients [ 41 ]. More important information might be related to changes in the severity of hematuria [i.e.…”
Section: Which Kidney Surrogate Markers Are Used To Assess Renal Resp...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using repeated kidney biopsies in the case of persistent or worsening hematuria are essential to answer these questions. A small study with interval biopsies after a median time of 130 days indicated low agreement with clinically suspected active disease, which was found in only 41% of patients [ 41 ]. More important information might be related to changes in the severity of hematuria [i.e.…”
Section: Which Kidney Surrogate Markers Are Used To Assess Renal Resp...mentioning
confidence: 99%
“…A small study on repeated protocol kidney biopsies revealed a progression of the Berden score in almost all investigated cases, suggesting ongoing disease activity despite initiation of immunosuppressive therapy [ 72 ]. Sequential assessment of the Berden classification indicated a class switch in 50%, with a histologic progression reported in 30% [ 41 ]. Consequently, implementation of protocol biopsies might be a useful tool to determine therapy response.…”
Section: Can a Kidney Tissue Specimen Predict Kidney Function Recovery?mentioning
confidence: 99%
“…Clinical biomarkers, such as hematuria and serum creatinine do not reflect disease activity specifically and sensitively enough, thus they can be mistaken for relapses. Approximately half of the patients who underwent rebiopsy had alteration in the Berden classification, up-or downstepping in the classification hierarchy (105,106). This finding suggests that interval biopsy could aid clinicians to develop more appropriate and personalized treatment and predict kidney outcomes more precisely than the initial biopsy.…”
Section: Kidney Biopsymentioning
confidence: 99%
“…The inflammatory response seen in many diseases with immune deposits will eventually lead to chronic lesions with global glomerulosclerosis and interstitial fibrosis (IF) as characteristic features of common final pathways of kidney damage, if the respective processes are not terminated early 26 55. Repeat kidney biopsy (either protocol biopsies or as per indication) indicated that the number of globally sclerosed glomeruli and the proportion of patients with severe IF/tubular atrophy (IF/TA) increased in ANCA-GN with evidence of active disease despite immunosuppressive treatment 56. This indicates that despite treatment and clinical remission, sub-clinical inflammation and disease progression may still progress unnoticed.…”
Section: Presence Of Immune Deposits/complexes and Prognostication/th...mentioning
confidence: 99%